AN ANALYSIS OF UNIVERSITY STUDENTS ARGUMENTATIVE WRITING: FUNCTIONAL PERSPECTIVE - Hendriwanto Hendriwanto; Nurani Hartini; Joko Nurkamto; Ramnita Sharda (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2020)
This study aims to investigate the role of SFL theory in teaching academic writing. The present study was to find out what the change of genre awareness of students writing. Twenty-two participants were recruited to engage in the process of deconstruction, join construction, and independent construction activities. The findings of study revealed two important aspect in teaching academic writing, thematic Progression in students writing and appraisal concept in students writing argumentation. Data sources were gathered through student assignments to write argumentative essay. Student assignments were written in 6o minutes with the IELTS and TOEFL writing. Questionnaire and interviews in argumentative writing were given to students. Data were collected from students assignment and data were analysed through transitivity and appraisal system (Martin & White, 2015). This finding of the study implies to the language education particularly writing instruction.